Pengaruh Intervensi Strategi Pelaksanaan Keluarga terhadap Pengetahuan dan Kemampuan Keluarga dalam Merawat Klien Skizofrenia dengan Halusinasi - Susilawati Susilawati; Larra Fredrika (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2019)
This study aims to determine the effect of family implementation strategy interventions on family knowledge and ability to care for Schizophrenia clients with hallucinations in RSKJ Soeprapto Bengkulu. This study uses a quasi-experimental method with a one-group pre-test and post-test design, with a total sample of 15 respondents. The results of the analysis proved that there was an influence of implementation strategy interventions on family knowledge and abilities (p value = 0,000). Conclusion, family implementation strategy interventions are very important to note and must be implemented as a form of intervention to improve family knowledge and abilities in caring for Schizophrenia clients, so clients who have returned home can be cared for properly and correctly by the family, and the family can immediately decide for clients to get treatment again if there is a recurrence. Keywords: Family, Schizophrenia, Hallucinations, Implementation Strategy